Multilayer pipe

JP7637005B2Active Publication Date: 2025-02-27SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021132636
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-17
Publication Date
2025-02-27
Estimated Expiration
2041-08-17

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、物性低下を抑制し、高い耐火性能を有する多層管を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637005000002
    Figure 0007637005000002
  • Figure 0007637005000003
    Figure 0007637005000003
  • Figure 0007637005000004
    Figure 0007637005000004
Patent Text Reader

Abstract

To provide a multilayer pipe capable of suppressing deterioration of physical properties and having high fire resistance.SOLUTION: A multilayer pipe comprises an inner layer 1, an intermediate layer 2 arranged outside the inner layer 1, and an outer layer 3 arranged outside the intermediate layer 2. The intermediate layer 2 contains polyvinyl chloride resin, thermally expandable graphite and zeolite. The content of the thermally expandable graphite is 5 pts.mass to 20 pts.mass with respect to 100 pts.mass of the polyvinyl chloride resin, and the content of the zeolite is 0.5 pt.mass to 3.0 pts.mass with respect to 100 pts.mass of the polyvinyl chloride resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-layer pipe. [Background technology]

[0002] In buildings, as construction technology becomes more sophisticated, piping materials are required to have a variety of properties, and multi-layer pipes are used. Multi-layer pipes as piping materials are required to have high fire resistance, for example, for use in fire compartments.

[0003] A specific function of fire resistance required for piping materials is that the piping material expands due to the heat of fire, blocking the piping itself and preventing the spread of fire through the piping material. As such a piping material, a piping material containing thermally expandable graphite has been proposed (for example, see Patent Document 1).

[0004] In recent years, the use of PVC pipes, which are lightweight and easy to install, has become mainstream as a piping material. Furthermore, due to market conditions, the demand for standpipes, which require a large diameter, is increasing, so there is a need to have a large diameter product lineup. PVC pipes achieve their fire resistance by burning and leaving residue that clogs the pipes, but generally, as the diameter increases, the area that becomes clogged with burnt PVC residue when exposed to the heat of a fire increases, making it more difficult for the pipes to achieve fire resistance. If the amount of thermally expandable graphite added is increased in order to improve fire resistance, there is a problem that the physical properties of the multi-layer pipe are reduced, such as a decrease in tensile strength due to the thermally expandable graphite acting as a crack initiation point, or a decrease in mechanical strength due to increased flatness of the thermally expandable graphite. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-74689 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above circumstances, an object of the present invention is to provide a multi-layer pipe that suppresses deterioration of physical properties and has high fire resistance. [Means for solving the problem]

[0007] As a result of intensive research to achieve the above object, the inventors have found that by blending a predetermined amount of thermally expandable graphite in the intermediate layer and providing a predetermined uneven portion in the outer layer, it is possible to suppress the deterioration of physical properties and obtain a multi-layer pipe with high fire resistance. Based on this finding, the inventors have further researched and completed the present invention.

[0008] The present invention has been made to solve the above problems, and the gist of the present invention is as follows. [1] A multi-layer pipe comprising an inner layer, an intermediate layer disposed outside the inner layer, and an outer layer disposed outside the intermediate layer, the intermediate layer containing a polyvinyl chloride resin, thermally expandable graphite, and a zeolite, the thermally expandable graphite content being 5 parts by mass to 20 parts by mass per 100 parts by mass of the polyvinyl chloride resin, and the zeolite content being 0.5 parts by mass to 3.0 parts by mass per 100 parts by mass of the polyvinyl chloride resin. [2] A thermally expandable material is adsorbed on the cavity wall surface of the zeolite, The multi-layer tube according to [1], wherein the total amount of gas generated when the thermally expandable material is heated to 220°C to 500°C is 0.6 mmol / g or more. Effect of the Invention

[0009] According to the present invention, it is possible to provide a multi-layer pipe which is suppressed from deteriorating in physical properties and has high fire resistance. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view of a multi-layer tube according to an embodiment of the present invention. [Diagram 2]1 is a plan view showing an example of a multi-layer pipe manufacturing apparatus according to an embodiment of the present invention. [Diagram 3] 1 is a front view showing an example of a multi-layer pipe manufacturing apparatus according to an embodiment of the present invention. [Figure 4] 1 is a configuration diagram showing an example of a mold and a tube for forming the outer surface of a multi-layer pipe used in a manufacturing apparatus for a multi-layer pipe according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Multilayer pipe] As shown in Fig. 1, a multi-layer pipe 10 according to an embodiment of the present invention includes an inner layer 1, an intermediate layer 2, and an outer layer 3. The inner layer 1 constitutes the innermost layer of the multi-layer pipe 10, and the outer layer 3 constitutes the outermost layer of the multi-layer pipe 10. The multi-layer pipe 10 shown in Fig. 1 has a multi-layer structure in which the inner layer 1, intermediate layer 2, and outer layer 3 are laminated in this order from the inside of the multi-layer pipe. Note that the structure of the multi-layer pipe 10 is not limited to three layers, and for example, the intermediate layer 2 may be multiple layers.

[0012] The overall thickness of the multi-layer pipe 10 is preferably 3.5 mm to 9.0 mm, more preferably 3.7 mm to 8.8 mm, and even more preferably 4.0 mm to 8.5 mm. When the overall thickness of the multi-layer pipe 10 is within the above range, it has a thickness equivalent to a general VP nominal diameter of 40 to 150, and can be joined to general joints.

[0013] The thickness of the inner layer 1 is preferably from 0.5 mm to 3.2 mm, more preferably from 0.7 mm to 3.0 mm, and further preferably from 0.9 mm to 2.5 mm. The thickness of the intermediate layer 2 is preferably from 0.5 mm to 4.0 mm, more preferably from 0.7 mm to 3.5 mm, and further preferably from 0.9 mm to 3.2 mm. The thickness of the outer layer 3 is preferably 0.5 mm to 3.2 mm, more preferably 0.7 mm to 3.0 mm, and further preferably 0.9 mm to 2.5 mm.

[0014] The inner layer 1, the intermediate layer 2, and the outer layer 3 constituting the multi-layer pipe 10 contain polyvinyl chloride resin. Among them, the intermediate layer 2 contains polyvinyl chloride resin, thermally expandable graphite, and zeolite. By including polyvinyl chloride resin, thermally expandable graphite, and zeolite in the intermediate layer 2, the multi-layer pipe 10 can have high fire resistance. By including thermally expandable graphite in the intermediate layer 2, it is possible to suppress a decrease in tensile strength due to cracks caused by the thermally expandable graphite being the crack origin, and it is possible to suppress a decrease in mechanical strength due to an increase in the flatness of the thermally expandable graphite. In addition, by including zeolite to which a thermally expandable material is adsorbed in the intermediate layer 2, it is possible to increase the strength of the combustion residue, and improve fire resistance by expanding the residue by vaporizing ammonia, etc., which is a thermally expandable material adsorbed on the cavity walls constituting the cavities of the zeolite, by heat.

[0015] (Polyvinyl chloride resin) As materials for forming the inner layer 1, the intermediate layer 2 and the outer layer 3, polyvinyl chloride resins are preferably used. Examples of polyvinyl chloride resins include (1) polyvinyl chloride homopolymers, (2) copolymers of vinyl chloride monomers and monomers having unsaturated bonds copolymerizable with the vinyl chloride monomers, and (3) graft copolymers in which vinyl chloride is graft-copolymerized with a (co)polymer other than vinyl chloride, and these may be used alone or in combination of two or more. If necessary, the polyvinyl chloride resins may be chlorinated.

[0016] The above (2) monomer having an unsaturated bond copolymerizable with the vinyl chloride monomer is not particularly limited, and examples thereof include α-olefins such as ethylene, propylene, butylene, etc.; vinyl esters such as vinyl acetate, vinyl propionate, etc.; vinyl ethers such as butyl vinyl ether, cetyl vinyl ether, etc.; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl acrylate, etc.; aromatic vinyls such as styrene, α-methylstyrene, etc.; N-substituted maleimides such as N-phenylmaleimide, N-cyclohexylmaleimide, etc.; and the like. These may be used alone or in combination of two or more kinds.

[0017] The above (3) copolymer to be graft-copolymerized with vinyl chloride is not particularly limited as long as it is a copolymer to be graft-copolymerized with vinyl chloride, and examples thereof include ethylene-vinyl acetate copolymer, ethylene-vinyl acetate-carbon monoxide copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate-carbon monoxide copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, acrylonitrile-butadiene copolymer, polyurethane, chlorinated polyethylene, chlorinated polypropylene, and the like. These may be used alone or in combination of two or more kinds.

[0018] The average polymerization degree of the polyvinyl chloride resin is not particularly limited, but a smaller average polymerization degree leads to a decrease in the physical properties of the molded product, while a larger average polymerization degree leads to an increase in melt viscosity making molding difficult, so that the average polymerization degree is preferably 400 to 1,600, more preferably 500 to 1,500, and even more preferably 600 to 1,400. The above-mentioned average degree of polymerization means an average degree of polymerization measured in accordance with JIS K 6720-2:1999 "Plastics-Vinyl chloride homopolymer and copolymer (PVC)-Part 2: Preparation of test pieces and determination of properties" using a resin obtained by dissolving a vinyl chloride resin in tetrahydrofuran (THF), removing insoluble components by filtration, and then drying and removing the THF in the filtrate.

[0019] The polymerization method for the polyvinyl chloride resin is not particularly limited, and any conventionally known polymerization method can be used, such as bulk polymerization, solution polymerization, emulsion polymerization, and suspension polymerization.

[0020] The method for chlorinating the polyvinyl chloride resin is not particularly limited, and any conventionally known chlorination method can be used, such as a thermal chlorination method and a photochlorination method.

[0021] Any of the above polyvinyl chloride resins may be crosslinked or modified to the extent that the fire resistance of the resin composition is not impaired. In this case, a resin that has been crosslinked or modified in advance may be used, or may be crosslinked or modified at the same time as the additives are blended, or may be crosslinked or modified after the above components are blended into the resin. There is no particular limitation on the method for crosslinking the above resin, and examples of the method include ordinary crosslinking methods for polyvinyl chloride resins, such as crosslinking using various crosslinking agents or peroxides, crosslinking by electron beam irradiation, and methods using water-crosslinkable materials.

[0022] (Thermal Expandable Graphite) The thermally expandable graphite contained in the vinyl chloride resin composition constituting the intermediate layer 2 is flaky, spherical, or other thermally expandable graphite. Thermally expandable graphite expands when heated, and is produced by treating powders of natural scaly graphite, pyrolytic graphite, kish graphite, or the like with an inorganic acid and a strong oxidizing agent to generate a graphite intercalation compound, which is a type of crystalline compound that maintains the layered structure of carbon. Examples of inorganic acids include concentrated sulfuric acid, nitric acid, and selenic acid. Examples of strong oxidizing agents include concentrated nitric acid, perchloric acid, perchlorates, permanganates, dichromates, and hydrogen peroxide. The thermally expandable graphite obtained by the acid treatment as described above may be further neutralized with a neutralizing agent such as ammonia, an aliphatic lower amine, an alkali metal compound, or an alkaline earth metal compound. Examples of the aliphatic lower amine include monomethylamine, dimethylamine, trimethylamine, ethylamine, propylamine, and butylamine. Examples of the alkali metal compounds and alkaline earth metal compounds include hydroxides, oxides, carbonates, sulfates, and organic acid salts of potassium, sodium, calcium, barium, magnesium, and the like. These may be used alone or in combination of two or more.

[0023] The expansion starting temperature of the thermally expandable graphite used in the present invention is preferably 150° C. or higher, more preferably 155° C. or higher, and even more preferably 160° C. or higher, from the viewpoint of preventing expansion except when a fire occurs. Moreover, from the viewpoint of increasing the volume increase rate of the thermally expandable graphite when a fire occurs and effectively exerting fire resistance, the temperature is preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower.

[0024] The content of the thermally expandable graphite in the vinyl chloride resin composition constituting the intermediate layer 2 is 5 parts by mass to 20 parts by mass relative to 100 parts by mass of the polyvinyl chloride resin. If the content of the thermally expandable graphite in the vinyl chloride resin composition constituting the intermediate layer 2 is less than 5 parts by mass relative to 100 parts by mass of the polyvinyl chloride resin, the thermal expandability of the intermediate layer 2 becomes insufficient, and sufficient fire resistance cannot be obtained. If the content of the thermally expandable graphite in the vinyl chloride resin composition constituting the intermediate layer 2 exceeds 20 parts by mass relative to 100 parts by mass of the polyvinyl chloride resin, the thermally expandable graphite becomes a crack starting point and causes cracks, resulting in a decrease in tensile strength, or the mechanical strength decreases due to an increase in the flatness of the thermally expandable graphite. The content of the thermally expandable graphite in the vinyl chloride resin composition constituting the intermediate layer 2 is preferably 6 parts by mass or more, more preferably 7 parts by mass or more, and even more preferably 8 parts by mass or more, relative to 100 parts by mass of the polyvinyl chloride resin. When the content of thermally expandable graphite is equal to or greater than the above lower limit, the thermal expandability of the intermediate layer 2 is sufficient. Furthermore, the content of thermally expandable graphite in the vinyl chloride resin composition constituting the intermediate layer 2 is preferably 18 parts by mass or less, more preferably 16 parts by mass or less, and even more preferably 15 parts by mass or less, per 100 parts by mass of the polyvinyl chloride resin. When the content of thermally expandable graphite is equal to or less than the above upper limit, the mechanical strength of the multi-layer pipe 10 is sufficient.

[0025] (Zeolite) There are no particular limitations on the skeletal structure of the zeolite contained in the vinyl chloride resin composition constituting the intermediate layer 2. Specific examples of the skeletal structure of the zeolite used in the present invention include A-type, ferrierite, MXM-22, ZSM-5, mordenite, L-type, Y-type, X-type, and beta-type, and the skeletal structure is one or more types selected from the above group. In addition, a thermally expandable material such as a gas or liquid may be adsorbed in advance on the cavity wall surface constituting the cavity of the porous structure of the zeolite. The type of the adsorbed thermally expandable material may be any number of types as long as it is one or more. When a thermally expandable material is adsorbed on the cavity wall surface constituting the cavity of the zeolite, the thermally expandable material adsorbed on the zeolite is vaporized by heat in the vinyl chloride resin, thereby making it possible to increase the expansion ratio.

[0026] The content of zeolite contained in the vinyl chloride resin composition constituting the intermediate layer 2 is 0.5 parts by mass to 3.0 parts by mass relative to 100 parts by mass of polyvinyl chloride resin. If the content of zeolite contained in the vinyl chloride resin composition constituting the intermediate layer 2 is less than 0.5 parts by mass relative to 100 parts by mass of polyvinyl chloride resin, the expansion property of the multilayer pipe and the residual strength after expansion become insufficient, and sufficient fire resistance cannot be obtained. If the content of zeolite in the vinyl chloride resin composition constituting the intermediate layer 2 exceeds 3.0 parts by mass relative to 100 parts by mass of polyvinyl chloride resin, the amount of inorganic matter added increases, leading to a decrease in mechanical strength. The content of zeolite contained in the vinyl chloride resin composition constituting the intermediate layer 2 is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, and even more preferably 1.0 parts by mass or more relative to 100 parts by mass of polyvinyl chloride resin. If the content of zeolite is equal to or more than the above lower limit, the expansion property of the multilayer pipe and the residual strength after expansion become sufficient. Furthermore, the content of zeolite in the vinyl chloride resin composition constituting the intermediate layer 2 is preferably 3.0 parts by mass or less, more preferably 2.7 parts by mass or less, and even more preferably 2.5 parts by mass or less, per 100 parts by mass of the polyvinyl chloride resin. By keeping the content of zeolite at or below the above upper limit, the amount of inorganic substances added can be suppressed, thereby suppressing a decrease in mechanical strength.

[0027] <Thermal expansion material> The thermally expandable material in the present invention is a material that is vaporized by heat, expanding the residue of the material that constitutes the intermediate layer, thereby improving fire resistance. It is preferable to use a thermally expandable material that does not gasify during molding (e.g., 220°C) but can be gasified during combustion (e.g., 500°C). For example, ammonia (NH 3 ) and nitrogen (N 2 ) is a nitrogen-containing compound.

[0028] The amount of the thermally expandable material adsorbed on the cavity wall surface of the zeolite is preferably 0.6 mmol / g or more, more preferably 0.9 mmol / g or more, and even more preferably 1.2 mmol / g or more. When the amount of the thermally expandable material adsorbed on the cavity wall surface of the zeolite is equal to or more than the above lower limit, the multi-layer tube has sufficient expandability and can improve fire resistance. In addition, the amount of the thermally expandable material adsorbed on the cavity wall surface of the zeolite is preferably 0.9 mmol / g or less, more preferably 1.2 mmol / g or less, and even more preferably 1.5 mmol / g or less. When the amount of the thermally expandable material adsorbed on the cavity wall surface of the zeolite is equal to or less than the above upper limit, the multi-layer tube can be prevented from excessively expanding, and the residual strength after expansion becomes sufficient. The amount of the thermally expandable material adsorbed on the cavity wall surface of the zeolite can be regarded as the total amount of gas generated when the thermally expandable material is heated to 220°C to 500°C, and can be measured by the method described in the examples below.

[0029] (Additives) The materials constituting the inner layer 1, intermediate layer 2, and outer layer 3 of the multi-layer pipe 10 of the present invention may contain additives such as inorganic fillers, lubricants, processing aids, impact modifiers, heat resistance improvers, antioxidants, light stabilizers, UV absorbers, pigments, plasticizers, thermoplastic elastomers, etc., within limits that do not impair the physical properties of the materials.

[0030] As the inorganic filler, a wide variety of known fillers can be used, and there is no particular limitation. Specific examples of the inorganic filler include silica, diatomaceous earth, alumina, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, barium carbonate, dawnnite, hydrotalcite, calcium sulfate, barium sulfate, gypsum fiber, calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass fiber, glass beads, silica-based balloon, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon fiber, carbon balloon, charcoal powder, various metal powders, potassium titanate, magnesium sulfate "MOS", lead titanate zirconate, aluminum borate, molybdenum sulfide, silicon carbide, stainless steel fiber, zinc borate, various magnetic powders, slag fiber, fly ash, and dewatered sludge.

[0031] As the lubricant, a wide variety of known lubricants can be used, and there is no particular limitation. Examples of lubricants include internal lubricants and external lubricants. The internal lubricant is used for the purpose of reducing the flow viscosity of the molten resin during molding and preventing frictional heat generation. The internal lubricant is not particularly limited, and for example, one or more selected from the group consisting of butyl stearate, lauryl alcohol, stearyl alcohol, epoxy soybean oil, glycerin monostearate, stearic acid, and bisamide can be used. The external lubricant is used for the purpose of increasing the sliding effect between the molten resin and the metal surface during molding. The external lubricant is not particularly limited, and for example, one or more selected from the group consisting of paraffin wax, polyolefin wax, ester wax, and montanic acid wax can be used.

[0032] The processing aid can be a wide variety of known ones and is not particularly limited. For example, acrylic processing aids such as alkyl acrylate-alkyl methacrylate copolymers having a weight average molecular weight of 100,000 to 2,000,000 can be mentioned. The acrylic processing aid is not particularly limited, and examples thereof include n-butyl acrylate-methyl methacrylate copolymers, 2-ethylhexyl acrylate-methyl methacrylate-butyl methacrylate copolymers, etc. These may be used alone or in combination of two or more kinds.

[0033] The impact modifier may be any of a wide variety of known ones, and is not particularly limited. For example, one or more selected from the group consisting of methyl methacrylate-butadiene-styrene copolymer (MBS), chlorinated polyethylene, acrylic rubber, etc. may be used.

[0034] The heat resistance improver may be any of a wide variety of known ones, and is not particularly limited. For example, α-methylstyrene-based and N-phenylmaleimide-based resins may be used.

[0035] The antioxidant is not particularly limited, and a wide variety of known antioxidants can be used, such as phenol-based antioxidants.

[0036] The light stabilizer is not particularly limited, and a wide variety of known light stabilizers can be used, such as hindered amine light stabilizers.

[0037] The ultraviolet absorbing agent is not particularly limited, and a wide variety of known ultraviolet absorbing agents can be used. For example, ultraviolet absorbing agents such as salicylic acid esters, benzophenones, benzotriazoles, and cyanoacrylates can be used. These agents may be used alone or in combination of two or more.

[0038] The pigment is not particularly limited, and a wide variety of known pigments can be used. For example, organic pigments such as azo, phthalocyanine, threne, and dye lake pigments; inorganic pigments such as oxide, molybdenum chromate, sulfide, selenide, and ferrocyanide pigments can be used. These pigments can be used alone or in combination of two or more.

[0039] A plasticizer may be added to the polyvinyl chloride resin. The plasticizer is not particularly limited, and a wide variety of known plasticizers can be used. For example, one or more selected from the group consisting of dibutyl phthalate, di-2-ethylhexyl phthalate, and di-2-ethylhexyl adipate can be used.

[0040] The thermoplastic elastomer is not particularly limited, and a wide variety of known elastomers can be used. For example, one or more selected from the group consisting of vinyl chloride thermoplastic elastomers such as acrylonitrile-butadiene copolymer (NBR), ethylene-vinyl acetate copolymer (EVA), ethylene-vinyl acetate-carbon monoxide copolymer (EVACO), vinyl chloride-vinyl acetate copolymer, and vinyl chloride-vinylidene chloride copolymer, styrene thermoplastic elastomers, olefin thermoplastic elastomers, urethane thermoplastic elastomers, polyester thermoplastic elastomers, and polyamide thermoplastic elastomers can be used.

[0041] The above-mentioned thermally expandable graphite, zeolite and additives can be mixed into the polyvinyl chloride resin by a wide variety of known methods, including hot blending and cold blending.

[0042] <Applications of multi-layer pipes> The multi-layer pipe 10 of the present invention obtained as described above is inhibited from deteriorating in physical properties and has high fire resistance, and therefore can be suitably used as piping for buildings such as drainage pipes, ducts, and electric conduits. The multi-layer pipe 10 of the present invention can be suitably used not only as a constituent material for the main body of a pipe, but also as a constituent material for pipe joints.

[0043] <Manufacturing method of multi-layer pipe> Fig. 2 is a plan view showing a manufacturing apparatus 20 used to manufacture a multi-layer pipe 10 according to one embodiment of the present invention. Fig. 3 is a front view showing a manufacturing apparatus 20 used to manufacture a multi-layer pipe 10 according to one embodiment of the present invention. As shown in Figures 2 and 3, a manufacturing apparatus 20 for manufacturing a multi-layer pipe 10 includes an inner and outer layer extruder 11, an intermediate layer extruder 12, a die 13, a cooling water tank 15, a take-up machine 16, and a cutter 17. The die 13 is connected to the inner and outer layer extruder 11 and the intermediate layer extruder 12. The die 13 is connected to the cooling water tank 15. The take-up machine 16 is connected to the cooling water tank 15. The take-up machine 16 is connected to the cutter 17.

[0044] In the method for producing a multi-layer pipe of the present invention, first, the materials for the inner layer and the outer layer are fed into an inner / outer layer extruder 11 using a hopper, where the materials for the inner layer and the outer layer are melt-kneaded and extruded into a die 13. In addition, the material for the intermediate layer is fed into an intermediate layer extruder 12 using a hopper, where the material for the intermediate layer is melt-kneaded and extruded into a die 13.

[0045] Next, in the mold 13, the melt-kneaded mixture of the inner layer material, the outer layer material, and the melt-kneaded mixture of the intermediate layer material are heated to form an uncured multi-layer pipe having a three-layer structure. From the viewpoint of improving the fluidity of the inner layer material and the outer layer material, the heating temperature in the mold 13 is preferably 160°C or higher and 200°C or lower, more preferably 170°C or higher and 195°C or lower, and even more preferably 180°C or higher and 190°C or lower. The heating time in mold 13 is the time that the inner layer material and the outer layer material are present in mold 13, and from the viewpoint of improving the fluidity of the inner layer material and the outer layer material, it is preferably 3 minutes or more and 10 minutes or less, more preferably 4 minutes or more and 9 minutes or less, and even more preferably 5 minutes or more and 8 minutes or less.

[0046] Next, an uncured multi-layer pipe having a three-layer structure is extruded from the outlet of the mold 13 and sent to a cooling water tank 15. A tube 14 for forming the outer surface of a pipe is attached to the cooling water tank 15 to form the uncured multi-layer pipe into a predetermined size, and the outer surface of the uncured multi-layer pipe is cooled in contact with the tube 14 for forming the outer surface of the pipe. FIG. 4 is an enlarged cross-sectional view of the mold 13 and the tube 14 for forming the outer surface of the pipe in the manufacturing apparatus. As shown in FIG. 4, the inner layer material 21 and the outer layer material 23 melt-kneaded by the inner and outer layer extruder 11, and the intermediate layer material 22 melt-kneaded by the intermediate layer extruder 12 are injected into the mold 13 designed so that the outer peripheral edge of the cross-sectional shape of the intermediate layer becomes a perfect circle, and an uncured multi-layer pipe 10' is molded. The uncured multi-layer pipe 10' includes an uncured inner layer 31, an uncured outer layer 33, and an uncured intermediate layer 32 formed by the intermediate layer material 22. When the uncured multi-layer pipe 10' is discharged from the mold 13, the intermediate layer material 22 foams to form the uncured intermediate layer 32. The uncured multi-layer pipe 10' is inserted into a tube 14 for forming the outer surface of the pipe, and is cooled in a cooling water tank 15 while being molded to a predetermined size. In order to sufficiently harden the uncured multi-layer pipe 10', the cooling temperature in the cooling water tank 15 is preferably 14°C or higher and 26°C or lower, more preferably 16°C or higher and 24°C or lower, and even more preferably 18°C ​​or higher and 22°C or lower. The cooling time in the cooling water tank 15 is the time that the uncured multilayer pipe 10' remains in the cooling water tank 15, and from the viewpoint of sufficiently curing the inner layer material and the outer layer material, it is preferably from 4 minutes to 16 minutes, more preferably from 6 minutes to 14 minutes, and even more preferably from 8 minutes to 12 minutes.

[0047] Next, the multi-layer pipe 10 cooled in the cooling water tank 15 is taken up by a take-off machine 16, and the multi-layer pipe 10 sent from the take-off machine 16 is cut to a predetermined length by a cutter 17. In this manner, a multi-layer pipe 10 having a predetermined length is obtained.

[0048] Although the embodiment of the present invention has been described above, the present invention is not limited to these examples, and it is needless to say that the present invention can be embodied in various forms without departing from the gist of the present invention. EXAMPLES

[0049] Hereinafter, the embodiments of the present invention will be described more specifically based on examples, but the present invention is not limited to these.

[0050] Examples and Comparative Examples Based on the composition shown in Table 1 below, the mixture was roll-mixed for 3 minutes using an 8-inch mixing roll (manufactured by Yasuda Seiki Seisakusho) at 190°C, then press-molded for 3 minutes using a press machine (manufactured by Toho Machinery Co., Ltd.) at 200°C, and then cooled for 3 minutes using a cooling press machine (manufactured by Toho Machinery Co., Ltd.) at 20°C to prepare test pieces for each of the Examples and Comparative Examples with a thickness of 3.1 mm.

[0051] <Raw materials used> The materials used in the examples and comparative examples are as follows. <Polyvinyl chloride resin> ·Tokuyama Sekisui Co., Ltd. "TS1000R" (average degree of polymerization: 1,000) <Light stabilizers> Nitto Kasei Co., Ltd. "TVS-8832" <Lubricant> Mitsui Chemicals, Inc. "HIWAX 220RKT" <Thermal Expandable Graphite> ·Suzuhiro Chemical Co., Ltd. "GREP-EG" <Zeolite> Mizusawa Chemical Industries, Ltd. "Mizukalyzer DS" Tosoh Corporation "HSZ-300 341NHA", thermal expansion material "NH 3(220℃~500℃ total gas generation: 1.4mmol / g) Tosoh Corporation "HSZ-700 720NHA", thermal expansion material "NH 3 (220℃~500℃ total gas generation: 1.7mmol / g)

[0052] <Gas generation rate of thermal expansion materials> A test tube containing 1.0 g of zeolite containing a thermally expandable material was inserted into an oil bath set at the measurement temperature and heated for 5 minutes. The gas generated by thermal decomposition was collected using glassware, and the amount of gas generated was calculated from the volume of the gas generated at 20°C and 1 atmospheric pressure.

[0053] (Expansion ratio evaluation test) The test pieces were cut into a rectangular shape by roll pressing into a plate shape, and the thickness, length, and width were measured with a vernier caliper. The test pieces of each Example and Comparative Example were then placed in an electric furnace heated to 500°C for 3 minutes to expand. They were then taken out of the electric furnace and allowed to cool at room temperature. After cooling and expansion, the thickness, length, and width of the test pieces were measured with a vernier caliper, and the expansion ratio R was calculated by the following formula. If the expansion ratio R was 10 or more, it was determined that the thermal expansion coefficient was sufficient for practical use. Thermal expansion coefficient R=(a 1 ×b 1 ×c 1 ) / (a 0 ×b 0 ×c 0 ) a 0 : Thickness of test piece before expansion (mm) b 0 : Length of test piece before expansion (mm) c 0 : Width of test piece before expansion (mm) a 1 : Thickness of test piece after expansion (mm) b 1 : Vertical thickness of test piece after expansion (mm) c 1 : Lateral length of test piece after expansion (mm) <Judgment criteria> A: Expansion ratio R is 10 or more B: Expansion ratio R is 5 or more and less than 10 C: Expansion ratio R is less than 5

[0054] (Residue strength test) The test pieces were roll-pressed into plate-like shapes and cut into rectangular parallelepiped shapes with a length of 30±1 mm, width of 30±1 mm, and thickness of 3±0.1 mm. A hole of about 1 mm was drilled at the end of the sample, a wire was passed through it, and the sample was hung from a metal stand and placed in an electric furnace heated to 500°C for 3 minutes to create a combustion residue, which was then removed. Each test was repeated five times, and if the residue strength was low, it would fall off the stand. <Judgment criteria> A: 0 falls B: 1-2 falls C: 3 to 5 falls

[0055] (Tensile strength evaluation test) In accordance with JIS K 7161-1:2014 "Plastics - Determination of tensile properties - Part 1", test pieces for each Example and Comparative Example were prepared from the test specimen, and the tensile yield strength was measured at 5 mm / min. The measurement atmosphere was 23°C. The maximum load until the test piece broke was P (N), and the cross-sectional area of ​​the test piece was S (mm 2 ) and the tensile yield strength F (MPa) was calculated using the following formula. Tensile yield strength: F=P / S <Judgment criteria> A: Tensile yield strength F is 40 (MPa) or more B: Tensile yield strength F is 35 (MPa) or more and less than 40 (MPa) C: Tensile yield strength F is less than 35 (MPa)

[0056] (Ammonia temperature-programmed desorption measurement (NH 3 -TPD measurement) 1 g of the obtained test piece was cut out. The cut test piece was dissolved in tetrahydrofuran (THF), centrifuged, and the supernatant was removed. Unnecessary materials were dried and used as test pieces. When zeolite was mixed with other inorganic components, they were separated by known separation methods (sedimentation, filtration, etc.), and only zeolite was extracted to make an extracted test piece. 0.1 g of the extracted test piece was left to stand for 1 hour under a helium flow at 500°C, which was used as a pretreatment. After 1 hour of pretreatment, a mixed gas containing 5 volume % ammonia and 95 volume % helium was passed through the sample at room temperature to saturate and adsorb ammonia on the extracted test piece. After passing the mixed gas for 1 hour, the sample was heated to 100°C while passing helium gas instead of the mixed gas. After the temperature increase, the ammonia remaining in the atmosphere was removed by passing helium gas at 100°C for 0.5 hours. After removing the residual ammonia, the sample was heated to 500°C at a rate of 10°C / min under a helium flow rate of 30 mL / min, and the total amount of gas generated (mmol / g) when heated from 220°C to 500°C, measured during the heating process using a TCD detector, was taken as the amount of ammonia adsorbed by the sample.

[0057] [Table 1] [Explanation of symbols]

[0058] 1…Inner layer 2. Middle class 3…Outer layer 10…Multilayer pipe 10´…Unhardened fireproof pipe 11…Inner and outer layer extruder 12...Intermediate layer extruder 13...Mold 14...Tube for forming outer surface 15…Cooling water tank 16...Removal machine 17...Cutting machine 20…Manufacturing equipment 21…Inner layer material 23…Outer layer material 22...Intermediate layer material 31…Uncured inner layer 32…Uncured middle layer 33…Uncured outer layer

Claims

[Claim 1] The inner layer, an intermediate layer disposed on an outer side of the inner layer; an outer layer disposed outside the intermediate layer; the intermediate layer contains a polyvinyl chloride resin, thermally expandable graphite, and zeolite; The content of the thermally expandable graphite is 5 parts by mass to 20 parts by mass relative to 100 parts by mass of the polyvinyl chloride resin, The content of the zeolite is 0.5 parts by mass to 3.0 parts by mass relative to 100 parts by mass of the polyvinyl chloride resin, A thermally expandable material is adsorbed on a cavity wall surface of the zeolite, The thermally expandable material has a total gas generation amount of 0.6 mmol / g or more when heated to 220°C to 500°C.

Citation Information

Patent Citations

  • Multilayered fireproof pipe material

    JP2008180367A

  • Piping material for water supply and drainage

    JP2009074689A